The effectiveness of competition policy and the price-cost margin: Evidence from panel data - Patrick McCloughan; Seán Lyons; William Batt (The Economic and Social Research Institute (ESRI), 2007)
This paper presents robust panel data econometric evidence suggesting that more effective competition policy curtails the exercise of market power because countries in which competition policy is judged to be more effective are characterised by lower market price-cost margins, controlling for other factors, including market growth, import penetration and spare capacity. The measure of competition policy effectiveness incorporated into our analysis is the annual survey-based ratings of national competition authorities (NCAs) produced by Global Competition Review (GCR). Our findings imply a role for competition in enhancing economic competitiveness and that government should continue to support NCAs in enforcing competition policy.
Keywords: 330; Wettbewerbspolitik; Wirkungsanalyse; Panel; Schätzung; OECD-Staaten